On Elliptic equations with singular potentials and nonlinear boundary conditions - Ferreira, Lucas C.F.; Neves, Sérgio L.N. [UNESP] (My University, 2018)
We consider the Laplace equation in the half-space satisfying a nonlinear Neumann condition with boundary potential. This class of problems appears in a number of mathematical and physics contexts and is linked to fractional dissipation problems. Here the boundary potential and nonlinearity are singular and of power-type, respectively. Depending on the degree of singularity of potentials, first we show a nonexistence result of positive solutions in D1,2(ℝ+ n) with a Lp-type integrability condition on ∂ℝ+ n. After, considering critical nonlinearities and conditions on the size and sign of potentials, we obtain the existence of positive solutions by means of minimization techniques and perturbation methods.
Keywords: Elliptic equations; Existence and nonexistence problems; Nonlinear boundary conditions; Singular potentials